The Macroeconomic Effects of Quantitative Easing in the Euro Area: Evidence from an Estimated DSGE Model - Lukas Vogel; Stefan Hohberger; Romanos Priftis (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper analyses the macroeconomic effects of the ECB's quantitative easing using an open-economy DSGE model estimated with Bayesian techniques. Shock decompositions for real GDP growth and CPI inflation suggest positive contributions of up to 0.4 and 0.5 pp in the standard linearized version of model. Using piecewise linear solution techniques to allow for an occasionally binding zero-bound constraint raises the positive impact on growth and inflation to 0.8 and 0.7 pp.
Keywords: E52; 330